The electrochemical and theoretical studies of corrosion inhibition of aluminium in acidic and basic solutions by Benzene-1,2,4,5- Tetracarboxylic dianhydride (PMDH) / Zohreh Shahnavaz - Shahnavaz, Zohreh (2009)
The inhibitory activity of benzene -1, 2, 4, 5-tetracarboxylic dianhydride(pyromellitic dianhydride) on aluminium corrosion in hydrochloric acid (1.0 M HCl), sodium chloride (1.0 M NaCl) and potassium hydroxide (1.0 M KOH) was measured by means of electrochemical techniques such as electrochemical impedance spectroscopy(EIS) and polarization curves. The surface morphology was studied using scanning electron microscopy (SEM). The results indicate that benzene -1, 2, 4, 5-tetracarboxylic dianhydride suppress aluminium corrosion in these three media by its adsorption on the aluminium surface according to Langmuir adsorption isotherm. Potentiodynamic and EIS measurements indicate that the inhibition efficiency increases with the decrease in temperature and increase in the concentration of the inhibitor. On the other hand quantum chemical calculations show a correlation between molecular parameters and the corrosion behavior of PMDH.